[Beggars ; Putok ; Sto. Nino squatters ; Baclaran vendors ; Timbangan ; Airport taxis [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Tackles Igorot beggars from the Cordilleras who flock to Manila; laws in cottage industry that sets the issue on fire and ban on the manufactuer and sale of fireworks; the squatters on Meralco Ave. Sitio Sto. Nino Pasig City; the ambulant vendors in Baclaran; the cheating in the use of weighing scales in wet market; and the story of an airport taxi service accused of overcharging and discrimination against Filipinos.